Multiple Conceptual Modelling of Perceived Quality of In-flight Airline Services - Šebjan, Urban; Tominc, Polona; Širec, Karin (Promet - Traffic&Transportation, 2017)
Despite growing literature on the different aspects of airline service quality in relation to behavioural intentions, less attention has been paid to some specific aspects of in-flight services. The focus of the present research is, therefore, on a multiple conceptual model of the quality of in-flight services in relation to passengers’ perception of value, followed by recommendations (word of mouth - WOM) of airlines, as well as the quality and comfort of airline seats. The study is performed using two databases of reviewers’/passengers’ opinions regarding the quality of in-flight airline services and airline seat comfort. Our research results reveal that the perceived comfort of the airplane seat is the most important factor of passengers’ perceived quality of in-flight airline services, which also considerably affects the passengers’ perception of value, and consequently moderates behavioural intentions (in our research, expressed through positive WOM). The analysis of the relative importance of the components of perceived airline seats’ comfort shows that seat width is the most significant factor that contributes to the overall perceived comfort of the airline seat.